Pengembangan Aplikasi Kasir untuk Mengatasi Keterbatasan Sistem Transaksi Manual di Daanish Store Banyuwangi dengan Metode Waterfall - Aslamiyah, Sulaibatul; Sumitro, Arif Hadi (Jurnal Informatika dan Komputer, 2025)
A cash application is something that is very necessary in the business world. No exception to the Daanish Store, which really needs a cash app. Daanish Store is an enterprise that sells school supplies, office tools, college supplies and school equipment. Currently, the registration of sales at the Daanish Store still uses manual methods. The sales are recorded on a book and recorded every weekend. The stock of goods could not be controlled because the shop employees hardly ever recorded the stock of remaining goods. Employees only report if there are exhausted items to ask for immediate return. Thus, the owner of the Daanish Store can't know how much cancellation is obtained and cannot control the stock of goods. Based on the problems faced by Daanish Store, research was carried out on the development of cash application. The system is built using the waterfall method with stages of requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing and operation and maintenance. The decommissioned system can be used to record sales, stock goods and present sales reports. The result of this research is a web-based cashier application that can help solve the problems faced by Daanish Store.